Upregulation of RANTES Gene Expression in Neuroglia by Japanese Encephalitis Virus Infection - Chen, Chun-Jung (American Society for Microbiology, 2004)
Infection with Japanese encephalitis virus (JEV) causes cerebral inflammation and stimulates inflammatory cytokine expression. Glial cells orchestrate immunocyte recruitment to focal sites of viral infection within the central nervous system (CNS) and synchronize immune cell functions through a regulated network of cytokines and chemokines. Since immune cell infiltration is prominent, we investigated the production of a responding chemoattractant, RANTES (regulated upon activation, normal T-cell expressed and secreted), in response to JEV infection of glial cells. Infection with JEV was found to elicit the production of RANTES from primary neurons/glia, mixed glia, microglia, and astrocytes but not from neuron cultures. The production of RANTES did not seem to be directly responsible for JEV-induced neuronal death but instead contributed to the recruitment of immune cells. RANTES expression required viral replication and the activation of extracellular signal-regulated kinase (ERK) as well as transcription factors, including nuclear factor kappa B (NF-κB) and nuclear factor IL-6 (NF-IL-6). The induction of RANTES expression by JEV infection in glial cells needed the coordinate activation of NF-κB and NF-IL-6. Using enzymatic inhibitors, we demonstrated a strong correlation between the ERK signaling pathway and RANTES expression. However, JEV replication was not dependent on the activation of ERK, NF-κB, and NF-IL-6. Altogether, these results demonstrated that infection of glial cells by JEV provided the early ERK-, NF-κB-, and NF-IL-6-mediated signals that directly activated RANTES expression, which might be involved in the initiation and amplification of inflammatory responses in the CNS.